2016
DOI: 10.1103/physrevd.94.084042
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-tensor teleparallel wormholes by Noether symmetries

Abstract: A gravitational theory of a scalar field non-minimally coupled with torsion and boundary term is considered with the aim to construct Lorentzian wormholes. Geometrical parameters including shape and redshift functions are obtained for these solutions. We adopt the formalism of Noether Gauge Symmetry Approach in order to find symmetries, Lie brackets and invariants (conserved quantities). Furthermore by imposing specific forms of potential function, we are able to calculate metric coefficients and discuss their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 57 publications
0
73
0
1
Order By: Relevance
“…where F is given by Eq. (42). On the other hand for the tangential component of the pressure we find the following result…”
Section: Energy Conditionsmentioning
confidence: 53%
“…where F is given by Eq. (42). On the other hand for the tangential component of the pressure we find the following result…”
Section: Energy Conditionsmentioning
confidence: 53%
“…Remembering here that the ordinary matter is not included in the field equations, i.e., ρ = p r = p t = 0. Therefore, we are not expecting that the conservation equation (31) or (32) due to the dark sector of the universe has the usual form.…”
Section: The Point-like Lagrangianmentioning
confidence: 99%
“…Still, there are few exact spherically symmetric solutions in modified Teleparallel gravity. Different authors have studied stars and wormholes in different Teleparallel theories [27,[31][32][33][34]. In [20,35], the authors found some vacuum exact solutions in f (T ) gravity, however, they imposed T = constant, which is nothing but consider GR plus a cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these symmetries could also help us in reducing the dynamics of a system and thus find exact solutions more easily. This method has been extensively used in the literature, both in cosmological and astrophysical scales [26][27][28][29][30][31][32][33][34][35][36]. Some cosmological paradigms such as quintessence and phantom ones can be recovered in the framework of f (R, G) theories of gravity [37].…”
Section: Introductionmentioning
confidence: 99%